Clinical and prognostic implications of high-sensitivity cardiac troponin T concentrations in type 2 non-ST elevation myocardial infarction. (April 2022) - Eggers, K.M.; Baron, T.; Gard, A.; Lindahl, B.
Abstract: Background: While the clinical importance of cardiac troponin is well-known in type 1 myocardial infarction (MI), evidence on this topic in type 2 MI is limited. We assessed the clinical and prognostic implications of high-sensitivity cardiac troponin (hs-cTnT) concentrations in a large sample of patients with type 2 MI. Methods: Retrospective registry-based cohort study (SWEDEHEART) including 4607 patients with type 2 MI and 43, 405 patients with type 1 MI, used for comparisons. Patients with ST-elevation MI were excluded. Multivariable-adjusted regressions were applied to investigate the associations of hs-cTnT concentrations (highest measured value during each hospitalization) with clinical variables and prognosis during a median follow-up of up to 1.9 years. Results: Hs-cTnT concentrations (median 264 [25th, 75th percentiles 112–654] ng/L) were significantly associated with various cardiovascular risk factors and comorbidities in type 2 non-ST elevation MI (NSTEMI) but only weakly with the underlying triggering condition. Most of these findings including the magnitude of hs-cTn release were similar to type 1 NSTEMI. Hs-cTnT (ln) independently predicted all-cause mortality (hazard ratio 1.13 [95% confidence interval 1.09–1.17]) and major adverse events (hazard ratio 1.13 [95% confidence interval 1.10–1.17]) in type 2 NSTEMI, similar as for type 1 NSTEMI according to interaction analysis. The associations of hs-cTnT (ln) with poor prognosis tended to be stronger in type 2 NSTEMI patients without known cardiovascular disease. Conclusions: Hs-cTnT concentrations independently predict adverse outcome in type 2 NSTEMI. The similarities to type 1 NSTEMI however, are striking and emphasize the difficulty to distinguish both MI types.